LABOR RESOURCES OF THE ENTERPRISE AND INNOVATIVE TECHNOLOGIES FOR THEIR MANAGEMENT - PIKHNIAK, Tetiana; DUNETS, Ivan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of the study is to substantiate theoretical provisions and practical proposals regarding the use of innovative technologies for personnel management at the enterprise. The topic of enterprise labor resources and innovative technologies for managing them is extremely relevant and is determined by modern trends of globalization, digitalization, and the rapid development of innovative technologies. In a changing economic environment, enterprises are faced with the need to improve the efficiency of human capital management to ensure competitiveness. The introduction of innovative technologies in the field of human resources management allows you to optimize the processes of recruitment, training, motivation and development of personnel, reduce costs and increase labor productivity. In addition, modern technologies, such as: HR process automation systems, data analytics, artificial intelligence and digital platforms, open up new opportunities for talent management and creating flexible forms of employment. This contributes to more effective use of human potential, adaptation to market challenges, and the formation of an innovative corporate culture. The study of the topic is relevant in view of the need to implement modern innovative approaches in the field of human resources management to ensure the sustainable development of enterprises in modern conditions of economic dynamics. The methodology for studying an enterprise’s labor resources and innovative technologies for managing them includes stages and methods aimed at comprehensive analysis and optimization of human capital management: analysis of the existing human resources management system (assessment of personnel policy, analysis of personnel selection processes), use of statistical analysis methods to determine quantitative and qualitative characteristics of human resources (number of personnel, dynamics of changes in personnel composition), analysis of modern tools for automating HR processes, assessment and analysis of application possibilities, effectiveness of implementing modern human resource management technologies. The article analyzes the staffing and use of personnel of a machine-building enterprise specializing in the production of technological equipment, LLC NVF «ADVISMASH». The movement of labor force in a manufacturing enterprise is studied. The importance of innovative technologies in the field of personnel management is highlighted. Modern HR technologies are outlined, classified by areas according to their functional purpose: selection and recruitment, personnel assessment, motivation, training, adaptation, communication, personnel accounting and talent management. The features and subsystems of management technologies in the field of personnel are characterized, in particular: outsourcing, outstaffing, personnel leasing, coaching, headhunting, recruiting, screening, direct search, reengineering, internal marketing, the "mystery shopper" method, automated personnel management systems and employee workstations. Attention is paid to HRM systems (human resource management systems), which are comprehensive platforms for centralized management of all aspects of personnel work, as well as for data analysis, employee productivity control, formation of personnel reserves, and automation of document flow. The application of artificial intelligence (AI) in the process of personnel selection is considered, in particular, in recruiting, which involves the use of AI algorithms to analyze large amounts of data from resumes, social networks, and profiles on platforms such as LinkedIn, which significantly reduces the time for searching for candidates and improves the quality of personnel decisions. To substantiate the effectiveness of innovations in the HR sector, coefficients and indicators were calculated: the overall efficiency coefficient of innovations implemented in the personnel management system, which allows analyzing the achieved results and trends in changes in the personnel policy of the enterprise, the absolute deviation of efficiency before and after implementation - to assess the dynamics of changes. An analysis of the growth rate of costs and the resulting effect was also conducted in order to determine the payback of innovative measures, obtaining the planned profit, and the possibility of further investment in the project. The practical value of the study lies in identifying effective ways to improve personnel management based on the implementation of innovative HRM technologies. An analysis of the effectiveness of the implementation of innovative HR management technologies at LLC NVF «ADVISMASH» demonstrates significant positive changes in the organization of personnel processes, especially in employee motivation. The implementation of modern HRM systems, flexible management approaches, digital educational platforms, and an improved motivation system contributed to increased labor productivity, reduced staff turnover, improved internal communication, and an overall increase in the efficiency of the enterprise. Further improvement of these tools will allow the Company to maintain its competitiveness in the market and maintain a high level of professional training of personnel. The results of the study can also serve as the basis for developing a new strategy for motivating personnel, forming an effective system of training and development of employees, as well as adapting the company’s personnel policy to dynamically changing market conditions, in particular due to the challenges of wartime .